Evaluation of surveillance of dengue fever cases in the public health centre of Putat Jaya based on attribute surveillance - Zumaroh, Zumaroh (Faculty of Public Health, 2015)
ABSTRACTDengue Hemorrhagic Fever (DHF) is a public health problem in the village of Putat Jaya which is an endemic area. Surveilans activity in DHF control program is the most important activity in controlling and monitoring disease progression. The program is expected to achieve incidence rate 55/100.000 population. Ths study aimed to evaluate the implementation of case surveilans in health centre of putat jaya based on attribute surveillance. Attribute surveillance is an indicator that describes the characteristics of the surveillance system. This research was an evaluation research with descriptive study design. As informants were clinic staff who deal specifically with cases of dengue hemorrhagic fever and laboratory workers. The techniques of data collection by interviews and document study. The variables of this study were simplicity, flexibility, acceptability, sensitivity, positive predictive value, representativeness, timeliness, data quality and data stability. It could be seen from Incidence Rate in 2013 has reached 133/100.00 population. The activity of surveilance in the village of Putat Jaya reviewed from disease contol program management was not succeed into decrease incidence rate of DHF. Therefore, dengue control programs in health centers Putat Jaya need to do cross-sector cooperation and cross-program cooperation, strengthening the case reporting system by way increasing in the utilization of information and communication technology electromedia.Keywords: case surveillance, dengue hemorrhagic fever, evaluation, attribute surveillance, Putat Jaya